Gastrin producing syngeneic mesenchymal stem cells protect non-obese diabetic mice from type 1 diabetes. (17th February 2022) - Gaudreau, Marie-Claude; Gudi, Radhika R.; Li, Gongbo; Johnson, Benjamin M.; Vasu, Chenthamarakshan
Abstract: Progressive destruction of pancreatic islet β-cells by immune cells is a primary feature of type 1 diabetes (T1D) and therapies that can restore the functional β-cell mass are needed to alleviate disease progression. Here, we report the use of mesenchymal stromal/stem cells (MSCs) for the production and delivery of Gastrin, a peptide hormone that is produced by intestinal cells and foetal islets and can increase β-Cell mass, to promote protection from T1D. A single injection of syngeneic MSCs that were engineered to express Gastrin (Gastrin-MSCs) caused a significant delay in hyperglycaemia in non-obese diabetic (NOD) mice compared to engineered control-MSCs. Similar treatment of early-hyperglycaemic mice caused the restoration of euglycemia for a considerable duration, and these therapeutic effects were associated with the protection of, and/or higher frequencies of, insulin-producing islets and less severe insulitis. While the overall immune cell phenotype was not affected profoundly upon treatment using Gastrin-MSCs or upon in vitro culture, pancreatic lymph node cells from Gastrin-MSC treated mice, upon ex vivo challenge with self-antigen, showed a Th2 and Th17 bias, and diminished the diabetogenic property in NOD- Rag1 deficient mice suggesting a disease protective immune modulation under Gastrin-MSC treatment associated protection from hyperglycaemia. Overall, this study shows the potential of production and delivery of Gastrin in vivo, by MSCs, in protecting insulin-producing β-cells and ameliorating the disease progression in T1D.